The role of interstitial carbon atoms on the strain-hardening rate of twinning-induced plasticity steels. (15th March 2020) - Luo, Z.C.; Huang, M.X.
Abstract: Synchrotron X-ray diffraction was applied to measure the dislocation density of two twinning-induced plasticity (TWIP) steels with different carbon content but comparable stacking fault energy (SFE). We found that the dislocation density of the carbon-alloyed TWIP is much higher than that of the carbon-free TWIP steel, though these two steels possess similar twin volume fraction. It indicates that the excellent tensile and strain-hardening properties of the carbon-alloyed TWIP steels are mainly caused by the high dislocation density induced by the carbon-dislocation interaction. Carbon-free TWIP steels are conventional low SFE fcc alloys similar to 316L stainless steel. Graphical abstract: Image, graphical abstract